Optogenetic approaches to vision restoration. (January 2019) - Simunovic, M.P.; Shen, W.; Lin, J.Y.; Protti, D.A.; Lisowski, L.; Gillies, M.C.
Abstract: Inherited retinal disease (IRD) affects about 1 in 3000 to 1 in 5000 individuals and is now believed to be the most common cause of blindness registration in developed countries. Until recently, the management of such conditions had been exclusively supportive. However, advances in molecular biology and medical engineering have now seen the rise of a variety of approaches to restore vision in patients with IRDs. Optogenetic approaches are primarily aimed at rendering secondary and tertiary neurons of the retina light-sensitive in order to replace degenerate or dysfunctional photoreceptors. Such approaches are attractive because they provide a "causative gene-independent" strategy, which may prove suitable for a variety of patients with IRD. We discuss theoretical and practical considerations in the selection of optogenetic molecules, vectors, surgical approaches and review previous trials of optogenetics for vision restoration. Optogenetic approaches to vision restoration have yielded promising results in pre-clinical trials and a phase I/II clinical trial is currently underway (ClinicalTrials.gov NCT02556736). Despite the significant inroads made in recent years, the ideal optogenetic molecule, vector and surgical approach have yet to be established. Highlights: Optogenetic approaches to vision restoration seek to restore vision to patients with inherited retinal diseases by rendering secondary and tertiary neurones of the retina light-sensitive. Two principal classes of molecule can be used: Type 1 (microbial) opsins or Type 2 (animal) opsins. Pre-clinical trials of optogenetic approaches in animal models suggest that the technique may restore vision in previously blind animals, with the threshold for activation being within 1-2 log units of the threshold for cone activation.